2015
DOI: 10.1007/s40368-015-0209-5
|View full text |Cite
|
Sign up to set email alerts
|

Molar incisor hypomineralisation: experience and perceived challenges among dentists specialising in paediatric dentistry and a group of general dental practitioners in the UK

Abstract: Both groups felt that MIH presents several clinical challenges and has a negative effect on the quality of life of the affected children and their families. There were significant differences in the views and perceptions between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
35
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 23 publications
4
35
1
4
Order By: Relevance
“…We found that PDs had twice the perception of patients with MIH lesions compared with GDPs, a situation re ected in countries such as Iraq 15 , Malaysia 22 , Australia-New Zealand 18 , Saudi Arabia 17 , China 8 and the UK 20 , where the prevalence of MIH is similar to Spain. Both in Spain and in other countries 15,17,18 , the general perception of dentists is that there is an increase in the incidence of MIH, although in our case the perception is signi cantly higher in PDs than in GDPs.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…We found that PDs had twice the perception of patients with MIH lesions compared with GDPs, a situation re ected in countries such as Iraq 15 , Malaysia 22 , Australia-New Zealand 18 , Saudi Arabia 17 , China 8 and the UK 20 , where the prevalence of MIH is similar to Spain. Both in Spain and in other countries 15,17,18 , the general perception of dentists is that there is an increase in the incidence of MIH, although in our case the perception is signi cantly higher in PDs than in GDPs.…”
Section: Discussionmentioning
confidence: 70%
“…The most recognized MIH lesion in both study groups was yellow/brown lesions, as it was in other countries 13,15−18 . This may be because white-cream lesions can be mistaken for other lesions such as uorosis or white spot cavities 20,24 . The percentage of post-eruptive enamel fractures was low, possibly because they may be confused with extensive cavity lesions, with atypical restorations typical of this pathology, since the enamel breaks quickly after rupture 15,25 , or with enamel hypoplasia, although in this case the edges of the lesion are not as irregular as in MIH 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that PDs had twice the perception of patients with MIH lesions compared with GDPs, a situation reflected in countries such as Iraq [ 15 ], Malaysia [ 22 ], Australia-New Zealand [ 18 ], Saudi Arabia [ 17 ], China [ 8 ] and the UK [ 20 ], where the prevalence of MIH is similar to Spain. Both in Spain and in other countries [ 15 , 17 , 18 ], the general perception of dentists is that there is an increase in the incidence of MIH, although in our case the perception is significantly higher in PDs than in GDPs.…”
Section: Discussionmentioning
confidence: 99%
“…The most recognized MIH lesion in both study groups was yellow/brown lesions, as it was in other countries [ 13 , 15 18 ]. This may be because white-cream lesions may be mistaken for other lesions, such as fluorosis or white spot cavities [ 20 , 29 ]. The percentage of post-eruptive enamel fractures was low, possibly because they may be confused with extensive cavity lesions, with atypical restorations typical of this pathology, since the enamel breaks quickly after rupture [ 15 , 30 ], or with enamel hypoplasia, although in this case the borders of the lesion are not as irregular as in MIH [ 20 ].…”
Section: Discussionmentioning
confidence: 99%